Analisis Rasio Keuangan pada Perusahaan Sektor Properti dan Real Estate di Bursa Efek Indonesia Tahun 2024 - Debora Desnia; Wahyu Muffti; Muhammad Rizal (Jurnal Ilmu Ekonomi dan Bisnis, 2026)
This study aims to analyze the financial performance of property and real estate sector companies listed on the Indonesia Stock Exchange in 2024 using four main financial ratios, namely Current Ratio (CR), Debt to Equity Ratio (DER), Return on Assets (ROA), and Total Asset Turnover (TATO). The study employs a descriptive quantitative approach using secondary data obtained from the financial statements of 92 companies published on the official website of the Indonesia Stock Exchange. The results show that the average CR of 7.86 indicates a high but uneven level of liquidity, the average DER of 0.79 reflects a relatively healthy capital structure, the average ROA of 0.02 indicates low profitability, and the average TATO of 0.15 suggests that asset utilization efficiency still needs improvement. There is a significant disparity in financial performance among companies within this sector